Comparison of various characteristics of women who do and do not attend for breast cancer screening. - Banks, E; Beral, V; Cameron, R; Hogg, A; Langley, N; Barnes, I; Bull, D; Reeves, G; English, R; Taylor, S; Elliman, J; Lole Harris, C (2002)
BACKGROUND: Information regarding the characteristics and health of women who do and do not attend for breast cancer screening is limited and representative data are difficult to obtain. METHODS: Information on age, deprivation and prescriptions for various medications was obtained for all women at two UK general practices who were invited to breast cancer screening through the National Health Service Breast Screening Programme. The characteristics of women who attended and did not attend screening were compared. RESULTS: Of the 1064 women invited to screening from the two practices, 882 (83%) attended screening. Screening attenders were of a similar age to non-attenders but came from significantly less deprived areas (30% of attenders versus 50% of non-attenders came from the most deprived areas, P < 0.0001) and were more likely to have a current prescription for hormone replacement therapy (32% versus 19%, P < 0.0001). No significant differences in recent prescriptions of medication for hypertension, heart disease, hypercholesterolaemia, diabetes mellitus, asthma, thyroid disease or depression/anxiety were observed between attenders and non-attenders. CONCLUSION: Women who attend the National Health Service Breast Screening Programme come from less deprived areas and are more likely to have a current prescription for hormone replacement therapy than non-attenders, but do not differ in terms of age or recent prescriptions for various other medications.